Entre o vir, o chegar e o partir: produção de alternativas entre o campo e a cidade – final do século XX e início do século XXI - Gonçalves , Karoline (2021)
This work aims to discuss alternatives visualized by individuals who experience/experienced living in the countryside, especially in western Paraná, between the end of the 20th century and the beginning of the 21st century. I seek to analyze how these people, who share a low possibility of capitalization, assess their own trajectories and, by doing so, elaborate rearrangements and reorganizations in their ways of living. I also deal with how these reconsiderations are permeated by pressures and expectations and the way in which a social movement, including between the countryside and the city, appears as one of the strategies adopted by most individuals throughout their experiences. Therefore, I try to show, through identification analysis, minutes of residents' associations and school documents, the protagonism of these individuals in deciding the best course to be taken, according to the desires and needs presented at every moment of their lives, leading them, moreover, to the simultaneity and volatility between different and unequal insertions in the countryside, due to the uncertainties experienced by them, arising from their class condition.